The oldest Calopterygidae in the Eocene Baltic amber (Odonata: Zygoptera) - Fleck, Günther; Waller, Alain; Serafin, Jacek; Nel, André (Zootaxa, 2009)
A larva of the damselfly family Calopterygidae is described from Eocene Baltic amber. It is the oldest record of this family partially filling the gap between previous records from the Oligocene and the Mesozoic inferred from molecular analyses for this family.